Ventriculosternal Shunt for the Treatment of Idiopathic Normal Pressure Hydrocephalus: A Case Report - Guo, Xinxia; Popal, Abdul Malik; Zhu, Zhoule; Cai, Chengwei; Lin, Jingquan; Jiang, Hongjie; Zheng, Zhe; Zhang, Jianmin; Shao, Anwen; Zhu, Junming (Frontiers in Surgery, 2021)
Background: Conventional corticospinal fluid (CSF) diversion surgery for idiopathic normal pressure hydrocephalus (iNPH) includes ventriculoperitoneal shunt and ventriculoatrial shunt. Ventriculosternal (VS) shunt may be considered if both the abdominal cavity and atrium are not feasible. Methods: A 76-year-old woman was admitted to our hospital with gait disturbance and urinary incontinence for 2 years, and the condition aggravated in the last 1 month. Based on clinical assessment and imaging findings, the patient was diagnosed with iNPH, with surgical indications. She was on peritoneal dialysis for chronic renal failure, and a cardiac Doppler echocardiogram showed enlargement of the left atrium and decreased diastolic function of the left ventricle. Due to these conditions, we chose the sternum as the vessel for CSF absorption and performed VS shunt. Results: No swelling, exudation, and effusion were found in the suprasternal fossa. Gait disturbance and urinary incontinence improved significantly immediately and 1 week after surgery, respectively. No shunt-related complication was reported at 16 months follow-up. Conclusion: This case demonstrated VS shunting as a feasible and alternative for the management of hydrocephalus.